1995
DOI: 10.1083/jcb.128.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Axonal synthesis of phosphatidylcholine is required for normal axonal growth in rat sympathetic neurons.

Abstract: Abstract. The goal of this study was to assess the relative importance of the axonal synthesis of phosphatidylcholine for neurite growth using rat sympathetic neurons maintained in compartmented culture dishes. In a double-labeling experiment [~4C]choline was added to compartments that contained only distal axons and [3H]choline was added to compartments that contained cell bodies and proximal axons. The specific radioactivity of labeled choline was equalized in all compartments. The results show that ,050% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…For example, in cultured cells choline deficiency causes apoptosis [Albright et al, 1996;Holmes-McNary et al, 1997] and inhibits axonal growth [Posse de Chaves et al, 1995], and treatments identical to those used in the current study alter hippocampal apoptotic patterns in vivo [Holmes-McNary et al, 1997]. Prenatal choline supplementation causes a 40% elevation in fetal brain phosphocholine [Garner et al, 1995], a metabolite that serves as a storage pool of choline and which may be necessary for cell division initiated by certain growth factors [Cuadrado et al, 1993;Jiménez et al, 1995;Kiss and Mukherjee, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cultured cells choline deficiency causes apoptosis [Albright et al, 1996;Holmes-McNary et al, 1997] and inhibits axonal growth [Posse de Chaves et al, 1995], and treatments identical to those used in the current study alter hippocampal apoptotic patterns in vivo [Holmes-McNary et al, 1997]. Prenatal choline supplementation causes a 40% elevation in fetal brain phosphocholine [Garner et al, 1995], a metabolite that serves as a storage pool of choline and which may be necessary for cell division initiated by certain growth factors [Cuadrado et al, 1993;Jiménez et al, 1995;Kiss and Mukherjee, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experiments carried out with in vitro preparations of growth cones have identified the existence of a population of large plasmalemma precursor vesicles that might be responsible for membrane expansion (Pfenninger and Friedman,1993). The possibility that at least the phospholipid components of the axonal plasma membrane are locally synthesized has also been raised (Posse de Chaves et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…10); we also recently have shown that ongoing GlcCer synthesis is required for basic fibroblast growth factor and laminin to stimulate axonal growth in hippocampal neurons (Boldin and Futerman, 1997). Similarly, phosphatidylcholine (PC) synthesis is required for the growth of sympathetic neurons (de Chaves et al, 1995). PC comprises ϳ40 -50% of total neuronal membrane lipids (Siegel et al, 1994), whereas SLs comprise between 15-20%.…”
Section: A Role For Glccer In Axon Growthmentioning
confidence: 99%